2017
DOI: 10.1016/j.retram.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after autologous adipose-derived stromal vascular fraction injection into fingers in systemic sclerosis patients

Abstract: Despite the limits of an open label study, the data are in favour of the long-term safety of the adipose-derived stromal vascular fraction injection. Two randomized double blind, placebo-controlled trials of this therapeutic agent are ongoing in the USA (NCT02396238) and in France (NCT02558543) and will help determine the place of this innovative therapy for SSc patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 6 publications
8
45
0
Order By: Relevance
“…For this indication, collection of cell samples and their expansion, transport, preparation, cryopreservation, shipment to site of use and subsequent injection have all been important considerations and are primary logistical challenges of their clinical use. Use of the ADRCs has also improved outcomes in patients with systemic sclerosis (5356) and improved healing of thermal burns (57). Cytori Therapeutics is developing ADRCs for thermal burn injury, including burns that are complicated by radiation exposure, and these ADRCs improved healing of full thickness burns in minipigs exposed to a sub-lethal dose of total body irradiation (TBI) – a radiation combined injury (58).…”
Section: Meeting Program Overview4mentioning
confidence: 99%
“…For this indication, collection of cell samples and their expansion, transport, preparation, cryopreservation, shipment to site of use and subsequent injection have all been important considerations and are primary logistical challenges of their clinical use. Use of the ADRCs has also improved outcomes in patients with systemic sclerosis (5356) and improved healing of thermal burns (57). Cytori Therapeutics is developing ADRCs for thermal burn injury, including burns that are complicated by radiation exposure, and these ADRCs improved healing of full thickness burns in minipigs exposed to a sub-lethal dose of total body irradiation (TBI) – a radiation combined injury (58).…”
Section: Meeting Program Overview4mentioning
confidence: 99%
“…Fat tissue can be easily and safely harvested and SVF can be collected bedside making it an attractive therapeutic option for physicians to offer to their patients [19]. A variety of publications have reported on the injection of SVF including: osteoarthritis [20, -21], degenerative disc disease [22], sclerosis [23], tendinopathy [24], congestive heart failure [25], chronic obstructive pulmonary disease (COPD) [26], radiation necrosis [27], xerostomia [28], psoriasis [29], and multiple sclerosis [30].…”
Section: Introductionmentioning
confidence: 99%
“…Comella et al reported on the safety of SVF in a variety of indications with various delivery methods. Other publications have demonstrated success of SVF for specific conditions including: chronic obstructive pulmonary disease (COPD) [17], congestive heart failure [18], degenerative disc disease [19], osteoarthritis/orthopedics [20][21][22][23][24], radiation necrosis [25], sclerosis [26], tendinopathy [27], xerostomia [28], psoriasis [29] and multiple sclerosis [30]. The following is a case report and to our knowledge first in man a single injection of SVF and PRP into a chronic non-healing stage 3 ulcer in a patient with an incomplete spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%